ANALISIS RASIO KEUANGAN ROA, ROE, PRICE EARNING RATIO TERHADAP UNDERPRICING SAHAM PERDANA. STUDI KASUS: PERUSAHAAN YANG MELAKUKAN IPO DI BEI PERIODE 2008 – 2011 - Alviani, Deska; Lasmana, Andy (Universitas Djuanda, 2015)
This research is aims to analyze the effect of financial ratios ROA, ROE, and the price earnings ratio (PER) of the IPO underpricing with the case study companies on the Stock Exchange IPO period from 2008 to 2011. This research used purposive sampling method and obtain research samples as many as 61 companies doing an IPO on the Stock Exchange. Methods of analysis of research data using descriptive statistics for the description of the object of research, test methods to assess the assumptions of classical regression equations, and to test hypotheses using ANOVA test for the F test and t-tesT. The test results showed simultaneous ROA, ROE, and PER has a significant effect on underpricing. In Partial ROA significant positive effect on underpricing, ROE significant negative effect on underpricing, and PER significant positive effect on underpricing.Keywords : Undepricing, Return On Asset, Return On Equity, dan Price Earning Ratio.